2013
DOI: 10.1021/tx300472d
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in Vitro Dendritic Cell-Based Test for Skin Sensitizer Identification

Abstract: The sensitizing potential of chemicals is currently assessed using animal models. However, ethical and economic concerns and the recent European legislative framework triggered intensive research efforts in the development and validation of alternative methods. Therefore, the aim of this study was to develop an in vitro predictive test based on the analysis and integration of gene expression and intracellular signaling profiles of chemical-exposed skin-derived dendritic cells. Cells were treated with four know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Regarding the effects of chemicals on JNK pathway, we observed a selective and marked increase in phospho-JNK levels following exposure to sensitizers, even more robustly than the activation observed for p38 MAPK. These results are in line with previous studies reporting a sustained phosphorylation of p38 MAPK and JNK following the treatment of the mouse fetal skin-derived dendritic cell line FSDC with the sensitizers DNFB, oxazolone, 1,4-phenylenediamine and NiSO 4 but not with irritants sodium dodecyl sulfate (SDS) and benzalkonium chloride (BC) [15] . Interestingly, a similar activation pattern was also observed in murine and human skin explants as well as in reconstituted skin models EST-100 and AST-200 [54] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the effects of chemicals on JNK pathway, we observed a selective and marked increase in phospho-JNK levels following exposure to sensitizers, even more robustly than the activation observed for p38 MAPK. These results are in line with previous studies reporting a sustained phosphorylation of p38 MAPK and JNK following the treatment of the mouse fetal skin-derived dendritic cell line FSDC with the sensitizers DNFB, oxazolone, 1,4-phenylenediamine and NiSO 4 but not with irritants sodium dodecyl sulfate (SDS) and benzalkonium chloride (BC) [15] . Interestingly, a similar activation pattern was also observed in murine and human skin explants as well as in reconstituted skin models EST-100 and AST-200 [54] .…”
Section: Discussionsupporting
confidence: 92%
“…RNA concentration was determined by OD 260 measurement using a NanoDrop spectrophotometer (Thermo Scientific, Wilmington, DE, USA) and samples stored in RNA Storage Solution at − 80 °C until use. Briefly, 1 μg of total RNA was reverse-transcribed using the NZY First-Strand cDNA Synthesis Kit and quantitative real-time PCR (qPCR) reactions were performed, in duplicate for each sample, on a Bio-Rad MyCycler iQ5 as previously described [15] . After amplification, a threshold was set for each gene and C t values were calculated for all samples.…”
Section: Methodsmentioning
confidence: 99%
“…Effects on CD86 were predominantly reported at the level of expression on the cell surface, and in transcriptomic studies, no general induction at the transcription level was reported: Clear effects at the mRNA level were noted in the studies on PBMC (Ryan et al 2004b), in PBMDC and MUTZ3 cells (Python et al 2009) and in THP-1 cells (Luis et al 2014), but not in other transcriptomic studies, e.g., by (Neves et al 2013). So far, no attempts at developing reporter cell lines mimicking this event by directly monitoring activation of the CD86 promoter were therefore reported.…”
Section: Expression Of Cell Surface Markersmentioning
confidence: 90%
“…The accumulated transcriptome data indicate that it is actually the molecular pathway most widely and reproducibly upregulated by sensitizers (Neves et al 2011), and multiple Nrf2-dependent genes were identified as key marker discriminating sensitizers from non-sensitizers and irritants. The gene most consistently identified is HMOX1 (coding for heme oxidase), which was induced by sensitizers in at least eight independent studies, in vitro (Ade et al 2009;Arkusz et al 2010;Emter et al 2013;Johansson et al 2011;Neves et al 2013;van der Veen et al 2013b;Vandebriel et al 2010) and ex vivo (van der Veen et al 2014a). …”
Section: Activation Of the Nrf2 Pathwaymentioning
confidence: 99%
“…Samples were stored in RNA Storage Solution at −80 °C until use. Total RNA (1 µg) was reverse-transcribed using the iScript Select cDNA Synthesis Kit and real-time reverse transcriptase-polymerase chain reaction (RT-PCR) reactions were performed, in duplicate for each sample, on a Bio-Rad MyCycler iQ5 (Hercules, CA, USA), as previously described by us [ 61 ]. After amplification, a threshold was set for each gene and Ct values were calculated for all samples.…”
Section: Methodsmentioning
confidence: 99%